(untitled) (The Insight, 2023)
Introduction: Nephrotic syndrome (NS) is a renal disorder primarily affecting children and characterized by significant proteinuria, low levels of albumin, edema, and high levels of serum cholesterol. Relapses are often triggered by infections, immunizations, and other factors that activate T-cells and increase cytokine production. Methods and materials: This case-control study was conducted at the Department of Pediatrics of Sylhet M.A.G. Osmani Medical College Hospital, Sylhet, for a duration of six months from June 2012 to December 2012. The study included a total of 80 pediatric patients, divided into two groups: the case group and the control group. The collected data were analyzed using Statistical Package for Social Sciences (SPSS), software, version-23.0. Results: In this study children in the FRNS group had a significantly lower mean age (4.05 ± 2.147 years) compared to the control group (5.175 ± 2.435 years) (p=0.0314). Early onset of nephrotic syndrome (age 1-5 years) was more common in the FRNS group (65%) than the control group (47.5%) (p<0.049). Frequent relapse was more prevalent in rural children (75%) than in urban children (55%) (p<0.05). The FRNS group had a significantly higher incidence of UTI and RTI (72%) compared to the control group (38%) (p<0.001). Serum albumin levels were significantly lower in the FRNS group (1.6 ± 0.2 gm/dl) than in the control group (2 ± 0.3 gm/dl) (p<0.001). Conclusion: Several risk factors are significantly associated with frequent relapse nephrotic syndrome (FRNS). These include poor socioeconomic status, rural residency, early age of onset, and low serum albumin at the time of the initial attack and infection.